Psychological wellbeing, Organisational support, and Job Satisfaction in Aviation professionals in South Africa - Mohottalalage, Isira Jayamanna (University of the Witwatersrand, Johannesburg, 2024)
The COVID-19 pandemic significantly disrupted the aviation industry, introducing new stressors for employees. This study examined relationships between psychological wellbeing, organizational support, and job satisfaction among 38 South African aviation professionals during the post-pandemic recovery period. Quantitative survey data was analysed using correlational and multiple regression techniques. Results revealed positive associations between organizational support, psychological wellbeing, and job satisfaction. In the multiple regression model, organizational support emerged as the strongest predictor, explaining over a quarter of variance in job satisfaction (β = .52, p < .001). This highlights its crucial buffering capacity amid acute pressures. Psychological wellbeing also exhibited a robust positive relationship with job satisfaction (β = .43, p < .01), emphasizing the importance of personal resources and positive appraisals for fulfilling work. Together, organizational support and psychological wellbeing significantly predicted job satisfaction, indicating their joint salience. Findings align with the job demands-resources model, with organizational and personal resources helping mitigate pandemic-related demands to sustain satisfaction and performance. Practical implications point to investing in supportive cultures, mental health provisions, and work-life balance policies to alleviate COVID-related strains as aviation companies rebuild. 4 However, limitations including the small sample size warrant caution in generalizing results. Addressing methodological constraints through expanded samples, longitudinal tracking, qualitative data, controlled experiments, and cross-national comparisons offers critical directions for subsequent research on optimizing occupational wellness in aviation during post pandemic transitions.
A research report submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Organizational Psychology to the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2024
Keywords: COVID-19 pandemic; Aviation industry; Psychological wellbeing; Organizational support; Job satisfaction; Post-pandemic recovery; Job demands-resources model; UCTD; SDG-8: Decent work and economic growth